2023
DOI: 10.1111/acel.13854
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the peripheral metabolic homeostasis and behavior in the TgF344‐AD rat model of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a growing public health concern in both the United States and the world. For Americans aged 65 or older, AD represents the fifth leading cause of death ("2020 Alzheimer's disease facts and figures," 2020), and it is estimated that over 80 million people worldwide will be living with some form of dementia by 2040 with AD comprising a majority of these (Ballard et al., 2011).AD is broadly characterized by an irreversible progressive loss of cognition and memory often accompanied by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
4
2
0
Order By: Relevance
“…Our finding that the TgF344‐AD rats in our study weighed more than WT controls is also not likely an artifact of the different vendors given that data from our colony and previously published research has shown that these rats weigh more than their WT littermates (Anckaerts et al, 2019; Srivastava et al, 2023). Our spontaneous alternation data and other published measures of activity (Cohen et al, 2013; Kelberman et al, 2022) do not suggest that these rats move less and expend less energy, although there is a report indicating that 6–12‐month‐old female but not male TgF344‐AD rats are hypoactive (Saré et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our finding that the TgF344‐AD rats in our study weighed more than WT controls is also not likely an artifact of the different vendors given that data from our colony and previously published research has shown that these rats weigh more than their WT littermates (Anckaerts et al, 2019; Srivastava et al, 2023). Our spontaneous alternation data and other published measures of activity (Cohen et al, 2013; Kelberman et al, 2022) do not suggest that these rats move less and expend less energy, although there is a report indicating that 6–12‐month‐old female but not male TgF344‐AD rats are hypoactive (Saré et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…The more severe pathology in females could be because of possible harmful consequences of cyclical increases in follicle-stimulating hormone (FSH) (Xiong et al, 2022) or double dosing of x-linked chromosome products such as x-linked ubiquitin-specific peptidase 11 (Yan et al, 2022). These differences may also result from impaired glucose clearance and reduced insulin sensitivity reported in young female but not male TgF344-AD rats (Srivastava et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The Tg female animals had higher body weights than WT females at the termination of the study at both 8- and 12-months of age, while the Tg males had greater body weights than WT males at the 8-month of age study termination. These results are consistent with other studies that have reported increased body weights in female TgF344-AD compared to WT rats [ 22 , 23 ]. In contrast, increased body weight in the male TgF344-AD rats was transitory since no differences in weight between genotypes were observed at 12 months of age and this finding is consistent with other studies that found no difference in body weight between TGF344-AD and WT male animals [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, others investigating the mouse microbiome did not report any changes in diversity with age (Binyamin et al., 2020 ). Beta diversity changes and modulation of community structure with age have been reported in another mice study (Binyamin et al., 2020 ) and our earlier rat study (Nagarajan et al., 2023 ; Srivastava et al., 2023 ). This is further evidence that the gut microbiota changes significantly with age.…”
Section: Discussionsupporting
confidence: 77%